Study on Comparative Analysis Regarding Genz’s Preference Among Dmart And Reliance Mart For Grocery Item In Ahemedabad City - Vivek Ladola; Khamar Harsh; Jignesh Vidani (Journal of Advanced Research in Economics and Business Management, 2025)
This study investigates the comparative preferences of Generation Z (Gen Z) consumers for grocery items at Dmart and Reliance Mart in Ahmedabad City. With the rapid evolution of shopping behaviors among younger consumers, understanding the factors influencing their choices between these two prominent retailers is crucial. The research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to capture a comprehensive view of Gen Z's shopping preferences. Key factors explored include price sensitivity, convenience, product variety, brand loyalty, and sustainability practices. Preliminary findings suggest that while Dmart is favored for its competitive pricing and extensive product range, Reliance Mart attracts Gen Z shoppers with its integrated online-offline shopping experience and innovative digital engagement. Additionally, sustainability emerges as a significant consideration, with many respondents expressing a preference for brands that align with their values. This study contributes to the existing literature by highlighting the unique attributes that influence Gen Z's grocery shopping choices in Ahmedabad and offers actionable insights for retailers seeking to enhance their marketing strategies and customer engagement efforts. Ultimately, understanding these preferences not only aids in better targeting but also fosters a deeper connection with this vital consumer demographic.